The Cambridge Introduction to Michel Foucault - Downing, Lisa (Cambridge University Press, 2013)
A reading of the works ofMichel Foucault (1926–84) does not so much equip us with new pieces of knowledge, or even teach us new and different ways of knowing. Rather, it invites us to share in a radical calling into question of the ways in which knowledge itself operates. Foucault argues that all forms of knowledge are historically relative and contingent, and cannot be dissociated from the workings of power